1992
DOI: 10.1111/j.1399-6576.1992.tb03553.x
|View full text |Cite
|
Sign up to set email alerts
|

Atracurium‐induced neuromuscular block in the isolated arm

Abstract: A modification of the isolated arm technique was applied in 10 females under opioid-based i.v. anaesthesia for comparison of the offset of an atracurium-induced neuromuscular block in an isolated arm to an arm with maintained circulation. The neuromuscular blocking effect of a bolus dose of atracurium 0.5 mg.kg-1 was measured bilaterally using the integrated adductor pollicis EMG response (integrated T1 EMG response in % of baseline value and T4/T1 ratio) after bilateral ulnar nerve train-of-four (TOF) stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…After 20 min of tourniquet inflation in patients receiving atracurium, peripheral venous pH remained within the physiological range (i.e. 7.34-7.42), and there was no difference between the two arms [8]. In the same study, the EMG response was not affected by tourniquet inflation for 20 min in the absence of neuromuscular blockers.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…After 20 min of tourniquet inflation in patients receiving atracurium, peripheral venous pH remained within the physiological range (i.e. 7.34-7.42), and there was no difference between the two arms [8]. In the same study, the EMG response was not affected by tourniquet inflation for 20 min in the absence of neuromuscular blockers.…”
Section: Discussionmentioning
confidence: 66%
“…In these studies, the drug was injected in the isolated forearm. In another study a tourniquet was inflated to assess recovery after systemic injection of atracurium [8]. The present study differed from these investigations in the role of the tourniquet.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is this question that we have examined. The previous suggested explanation, that the metabolism of atracurium in the effect compartment could explain this paradox, is improbable as the effect compartment is of small size and Ericksson and colleagues [6] have demonstrated that Hofmann degradation does not occur to any extent at the neuromuscular junction.…”
Section: Commentmentioning
confidence: 99%
“…It has been suggested that, because of the metabolism of atracurium, there is a different treatment of both drugs in the effect compartment [4,5]. However, there is no evidence that this occurs in vivo [6]. Various pharmacokinetic models have been constructed in an attempt to explain this phenomenon.…”
mentioning
confidence: 99%